ENGLISH FOR BUSINESS TRAINING FOR MANAGERS OF PARAPAT TOURISM OBJECT AT SIMALUNGUN REGENCY - Horia Siregar; Lai See May; Nurhasah Febriyanti Harahap; Anggi Wansyah Prayogi; Risnawaty; Yulia Arfanti (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
English for Business training for managers of Parapat tourism object in Simalungun Regency as a form of soft skills development in order to further increase professionalism in organizational business, because the tourism sector will be interact with many people. Following by business workers at Parapat tourist attraction in Simalungun Regency. The result of this Community Service is effective communication skills training which is very useful in improving self-quality, developing effective communication skills to support the sustainable of business. The location of this service is a tourist attraction for Parapat of Simalungun Regency. The method is lectures and practices.